Enhancing Computer Architecture Learning with a Spiral Curriculum - Pinho, Leonardo Bidese de; Domingues Júnior, Julio Saraçol (International Journal of Computer Architecture Education, 2024)
This paper presents preliminary experiences, particularly in developing competencies in the field of Computer Architecture and Organization (AOC), achieved through the application of the Active Methodology of Project-Based Learning (PBL) in the new spiral curriculum of the Computer Engineering (CE) course. It analyzes the perspective of students in third-semester courses: Integrative Project II (IP-2) and the new AOC. It highlights difficulties with teaching materials and the process of creating new materials focused on PBL, followed by a discussion on the formative paths and student performance observed through evaluation instruments and self-assessments. The conclusions highlight alignment with the desired characteristics for graduates, confirming the potential of adopting the spiral approach to improve learning in CE, particularly in AOC.